A kind of fluid loss reducing agent and preparation method thereof

By modifying the sulfonated humic acid, it cross-links it with β-cyclodextrin to form composite microspheres and combines with block polymers, the problem of the failure of existing filtration loss agents at high temperatures and insufficient anti-salt and calcium resistance is achieved, and better filtration loss performance is achieved.

CN119752425AActive Publication Date: 2025-04-04SHANDONG DESHUNYUAN PETROLEUM SCI&TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510260465.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The filter reduction agent of existing drilling fluid fails at high temperatures and has insufficient salt and calcium resistance, which cannot meet the needs of deep or ultra-deep wells.

Method used

By modifying the sulfonated humic acid, it is cross-linked with β-cyclodextrin to form composite microspheres and combine with block polymers, the anti-salt and calcium resistance is improved by using the role of the host and guest.

Benefits of technology

The high-temperature resistance and salt-resistant calcium resistance of the filter reducer are improved. The block polymer is released by the decomplexation of the host and guest at high temperatures, forming a dense mud cake, which significantly improves the filter loss performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fluid loss agents, and in particular to a fluid loss agent and a preparation method thereof. The fluid loss agent comprises the following raw materials in parts by weight: 40-45 parts of sulfonated humic acid, 10-12 parts of composite microspheres, 6-8 parts of block polymers, 0.1-0.12 parts of antibacterial agents and 0.2-0.3 parts of antioxidants; the humic acid is modified so that the composite microspheres are cross-linked with beta-cyclodextrin to form composite microspheres and are combined with block polymers, thereby solving the problem of insufficient high temperature resistance of the fluid loss agent, improving the salt and calcium resistance of the fluid loss agent through the host-guest interaction between the composite microspheres and the block polymers, and at the same time, at high temperature, the host-guest decomplexation can release the block polymer of the guest, thereby exerting better fluid loss reduction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluid loss agents, and in particular to a fluid loss agent and a preparation method thereof. Background Art

[0002] With the development of drilling engineering technology, the drilling depth has gradually increased, and the formations encountered have become increasingly complex, which has put forward higher requirements on the performance of drilling fluids. Among them, the filtration reduction performance of drilling fluids is particularly important. At present, commonly used water-based drilling fluid filtration reducers, such as starch and humic acid natural material filtration reducers, have low high temperature resistance due to the limitations of natural materials themselves. Such filtration reducers, such as sulfonated humic acid, often fail due to high temperature during use in deep or ultra-deep wells. At the same time, such filtration reducers have poor salt and calcium resistance and cannot be widely used to meet the increasing market demand. Summary of the invention

[0003] The object of the present invention is to provide a fluid loss reducer and a preparation method thereof. Humic acid is modified so that it is cross-linked with beta-cyclodextrin to form composite microspheres and combined with block polymers, thereby solving the problem of insufficient high temperature resistance of the fluid loss reducer, and improving the salt and calcium resistance of the fluid loss reducer through the host-guest interaction between the composite microspheres and the block polymers. At the same time, at high temperature, the host-guest decomplexation can release the guest block polymer, thereby exerting better fluid loss reduction performance.

[0004] The object of the present invention can be achieved by the following technical scheme: a fluid loss reducer and a preparation method thereof, comprising the following steps: weighing the following raw materials in parts by weight: 40-45 parts of sulfonated humic acid, 10-12 parts of composite microspheres, 6-8 parts of block polymers, 0.1-0.12 parts of antibacterial agents and 0.2-0.3 parts of antioxidants, mixing the sulfonated humic acid, composite microspheres, block polymers, antibacterial agents and antioxidants to prepare a fluid loss reducer; The sulfonated humic acid is sulfonated humic acid produced by Ryan Environmental Protection; The antibacterial agent is Haikuo HK-8360; The antioxidant is BASF Irganox 1330; The block polymer is prepared by the following steps: Step A1: p-nitroaniline, hydrochloric acid solution and deionized water are mixed, and sodium nitrite is added under stirring at a rate of 150-180 rpm and a temperature of 0-5° C., and the mixture is stirred for 15-20 min. Then, sodium hydroxide solution and phenol are added, and the mixture is heated to room temperature and reacted for 1.5-2 h to obtain intermediate 1. 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and tetrahydrofuran are mixed, and intermediate 1 is added under stirring at a rate of 100-120 rpm and room temperature, and the mixture is stirred for 3-4 h to obtain intermediate 2; The mass fraction of the hydrochloric acid solution is 35%, the molar concentration of the sodium hydroxide solution is 2 mol / L, the amount ratio of p-nitroaniline, hydrochloric acid solution, deionized water, sodium nitrite, sodium hydroxide solution and phenol is 0.05-0.054 mol: 15-18 mL: 20-25 mL: 0.054-0.055 mol: 45-48 mL: 0.05-0.054 mol; the amount ratio of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate 1 is 0.012-0.015 mol: 1.8-2 g: 0.1-0.12 g: 0.012-0.015 mol; During the reaction, under the action of hydrochloric acid solution and sodium nitrite, p-nitroaniline is diazotized, and then reacts with phenol to form an azo structure to obtain intermediate 1. Then, under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the hydroxyl group in intermediate 1 reacts with the carboxyl group in 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid to form an ester group to obtain intermediate 2. Step A2: Mix the intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and deionized water, stir and add azobisisobutyronitrile under nitrogen protection at 70°C, and react for 6-8h to obtain a block polymer; The ratio of intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile is 0.0008-0.001 mol: 0.01-0.012 mol: 0.28-0.3 mol: 0.09-0.1 mol: 0.01 g; During the reaction, under the action of azobisisobutyronitrile, the intermediate 2 containing a trithiocarbonate structure is used as a chain transfer agent, and through a reversible addition-fragmentation chain transfer method, under the action of an initiator azobisisobutyronitrile, it reacts with N-vinyl pyrrolidone containing a double bond, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid to obtain a block polymer; The composite microspheres are prepared by the following steps: Step B1: humic acid and potassium hydroxide solution are mixed, stirred at a stirring rate of 180-200 rpm, and ferric nitrate solution is added at room temperature, stirred for 15-20 minutes, then heated to 120-125° C., reacted for 3-4 hours, then sodium montmorillonite is added, ultrasonically dispersed for 20 minutes, and then the reaction is continued for 2-3 hours to obtain precursor 1; The molar concentration of potassium hydroxide solution is 4 mol / L, the molar concentration of ferric nitrate solution is 0.25 mol / L, and the dosage ratio of humic acid, potassium hydroxide solution, ferric nitrate solution and sodium montmorillonite is 0.8-1 g: 5-8 mL: 220-240 mL: 3.2-3.5 g; The humic acid is Ryan environmentally friendly humic acid; The sodium montmorillonite is Borui 800 mesh sodium montmorillonite; During the reaction, iron nitrate was used as the iron source, and an iron oxyhydroxide structure was formed by a hydrothermal method, and then compounded with humic acid and deposited on the surface of sodium montmorillonite and between the sheets to obtain precursor 1; Step B2: Precursor 1, Tween-20, Span-60 and kerosene are mixed, stirred at a stirring rate of 600-800 rpm, at room temperature, and stirred for 25-30 minutes to obtain an oil phase, β-cyclodextrin and sodium hydroxide solution are mixed, stirred at a stirring rate of 150-180 rpm, at room temperature, and epichlorohydrin is added, reacted for 1.5-2 hours to obtain an aqueous phase system, and then the aqueous phase system is added to the oil phase, heated to 70°C, and reacted for 6-8 hours to obtain composite microspheres; The amount ratio of precursor 1, Tween-20, Span-60 and kerosene is 3.2-3.5g:1.5-2g:1.5-2g:50-60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount ratio of β-cyclodextrin, sodium hydroxide solution, epichlorohydrin and oil phase is 9.8-10.4g:50-60mL:13-14g:150-160mL; During the reaction, in the sodium hydroxide solution, the hydroxyl groups in β-cyclodextrin and the epoxy groups in epichlorohydrin undergo a ring-opening reaction, and then the oil phase is added, and at the same time, the reverse emulsification method is used to allow the oxygen-containing groups in the humic acid in the precursor 1 to continue to react with epichlorohydrin and react with β-cyclodextrin, thereby cross-linking into balls to obtain composite microspheres; Beneficial effects of the invention: The invention discloses a fluid loss reducer and a preparation method thereof. By modifying humic acid and cross-linking it with β-cyclodextrin to form composite microspheres, the problem of insufficient high temperature resistance of the fluid loss reducer is solved, and the host-guest interaction between the composite microspheres and the block polymers is used to improve the salt and calcium resistance of the fluid loss reducer. At the same time, at high temperature, the host-guest decomplexation can release the guest block polymer, thereby exerting better fluid loss reduction performance; through cross-linking modification, the precursor 1 containing humic acid is cross-linked with β-cyclodextrin to form composite microspheres, and its three-dimensional structure can greatly improve the strength of its molecular structure, and due to the special The hydrophilic outer cavity and hydrophobic inner cavity further improve the thermal stability of the composite microspheres. Under high temperature conditions, with the dissociation of the host-guest binding between the terminal nitrobenzene block polymer and the composite microspheres containing cyclodextrin structure, the block polymer containing N-vinyl pyrrolidone, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid structure is released, and then adsorbed with clay particles by hydrogen bonds to form a clay-molecular chain-water molecule structure to form a dense mud cake, thereby showing good filtration loss reduction performance. Before the host and guest are dissociated, due to its own propanesulfonic acid anion group and the presence of its terminal azonitrobenzene, it can maintain good salt and calcium resistance. DETAILED DESCRIPTION

[0005] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0006] Example 1 A fluid loss reducer and a preparation method thereof, comprising the following steps: weighing the following raw materials in parts by weight: 40 parts of sulfonated humic acid, 10 parts of composite microspheres, 8 parts of block polymers, 0.1 parts of antibacterial agent and 0.2 parts of antioxidant, mixing the sulfonated humic acid, composite microspheres, block polymers, antibacterial agent and antioxidant to prepare a fluid loss reducer; The sulfonated humic acid is sulfonated humic acid produced by Ryan Environmental Protection; The antibacterial agent is Haikuo HK-8360; The antioxidant is BASF Irganox 1330; The block polymer is prepared by the following steps: Step A1: p-nitroaniline, hydrochloric acid solution and deionized water are mixed, and sodium nitrite is added under stirring at a rate of 150 rpm and a temperature of 0°C, and stirred for 15 minutes, and then sodium hydroxide solution and phenol are added, and the temperature is raised to room temperature, and the reaction is carried out for 1.5 hours to obtain intermediate 1, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and tetrahydrofuran are mixed, and intermediate 1 is added under stirring at a rate of 100 rpm and room temperature, and the reaction is carried out for 3 hours to obtain intermediate 2; The mass fraction of hydrochloric acid solution is 35%, the molar concentration of sodium hydroxide solution is 2 mol / L, the amount ratio of p-nitroaniline, hydrochloric acid solution, deionized water, sodium nitrite, sodium hydroxide solution and phenol is 0.05 mol: 15 mL: 20 mL: 0.054 mol: 45 mL: 0.05 mol; the amount ratio of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate 1 is 0.012 mol: 1.8 g: 0.1 g: 0.012 mol; Step A2: Intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and deionized water were mixed, stirred and azobisisobutyronitrile was added under nitrogen protection at 70°C, and reacted for 6 hours to obtain a block polymer; The ratio of intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile is 0.0008 mol: 0.01 mol: 0.28 mol: 0.09 mol: 0.01 g; The composite microspheres are prepared by the following steps: Step B1: Humic acid and potassium hydroxide solution were mixed, stirred at a stirring rate of 200 rpm, and ferric nitrate solution was added at room temperature, stirred for 15 minutes, then heated to 125° C., reacted for 3 hours, then sodium montmorillonite was added, ultrasonically dispersed for 20 minutes, and then continued to react for 2 hours to obtain precursor 1; The molar concentration of potassium hydroxide solution is 4 mol / L, the molar concentration of ferric nitrate solution is 0.25 mol / L, and the dosage ratio of humic acid, potassium hydroxide solution, ferric nitrate solution and sodium montmorillonite is 1 g: 5 mL: 240 mL: 3.2 g; The humic acid is Ryan environmentally friendly humic acid; The sodium montmorillonite is Borui 800 mesh sodium montmorillonite; Step B2: Precursor 1, Tween-20, Span-60 and kerosene were mixed, stirred at a stirring rate of 600 rpm and room temperature for 30 minutes to obtain an oil phase, β-cyclodextrin and sodium hydroxide solution were mixed, stirred at a stirring rate of 180 rpm and room temperature, and epichlorohydrin was added to react for 1.5 hours to obtain an aqueous phase system, and then the aqueous phase system was added to the oil phase, the temperature was raised to 70°C, and the reaction was performed for 8 hours to obtain composite microspheres; The dosage ratio of precursor 1, Tween-20, Span-60 and kerosene is 3.2g:2g:1.5g:60mL, the mass fraction of sodium hydroxide solution is 20%, and the dosage ratio of β-cyclodextrin, sodium hydroxide solution, epichlorohydrin and oil phase is 10.4g:50mL:14g:150mL.

[0007] Example 2 A fluid loss reducer and a preparation method thereof, comprising the following steps: weighing the following raw materials in parts by weight: 45 parts of sulfonated humic acid, 12 parts of composite microspheres, 6 parts of block polymers, 0.12 parts of antibacterial agents and 0.2 parts of antioxidants, mixing the sulfonated humic acid, composite microspheres, block polymers, antibacterial agents and antioxidants to prepare a fluid loss reducer; The sulfonated humic acid is sulfonated humic acid produced by Ryan Environmental Protection; The antibacterial agent is Haikuo HK-8360; The antioxidant is BASF Irganox 1330; The block polymer is prepared by the following steps: Step A1: p-nitroaniline, hydrochloric acid solution and deionized water are mixed, and sodium nitrite is added under stirring at a rate of 150 rpm and a temperature of 5°C, and stirred for 20 minutes. Then, sodium hydroxide solution and phenol are added, and the temperature is raised to room temperature, and the reaction is carried out for 1.5 hours to obtain intermediate 1. 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and tetrahydrofuran are mixed, and intermediate 1 is added under stirring at a rate of 120 rpm and room temperature, and the reaction is carried out for 3 hours to obtain intermediate 2; The mass fraction of hydrochloric acid solution is 35%, the molar concentration of sodium hydroxide solution is 2 mol / L, the amount ratio of p-nitroaniline, hydrochloric acid solution, deionized water, sodium nitrite, sodium hydroxide solution and phenol is 0.054 mol: 18 mL: 20 mL: 0.055 mol: 45 mL: 0.054 mol; the amount ratio of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate 1 is 0.015 mol: 1.8 g: 0.1 g: 0.015 mol; Step A2: Intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and deionized water were mixed, stirred and azobisisobutyronitrile was added under nitrogen protection at 70°C, and reacted for 6 hours to obtain a block polymer; The ratio of intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile is 0.001 mol: 0.01 mol: 0.3 mol: 0.09 mol: 0.01 g; The composite microspheres are prepared by the following steps: Step B1: Humic acid and potassium hydroxide solution were mixed, stirred at a stirring rate of 180 rpm, and ferric nitrate solution was added at room temperature, stirred for 15 minutes, then heated to 120° C., reacted for 3 hours, then sodium montmorillonite was added, ultrasonically dispersed for 20 minutes, and then continued to react for 2 hours to obtain precursor 1; The molar concentration of potassium hydroxide solution is 4 mol / L, the molar concentration of ferric nitrate solution is 0.25 mol / L, and the dosage ratio of humic acid, potassium hydroxide solution, ferric nitrate solution and sodium montmorillonite is 0.8 g: 5 mL: 220 mL: 3.2 g; The humic acid is Ryan environmentally friendly humic acid; The sodium montmorillonite is Borui 800 mesh sodium montmorillonite; Step B2: Precursor 1, Tween-20, Span-60 and kerosene were mixed, stirred at a stirring rate of 600 rpm and room temperature for 25 minutes to obtain an oil phase, β-cyclodextrin and sodium hydroxide solution were mixed, stirred at a stirring rate of 150 rpm and room temperature, and epichlorohydrin was added to react for 1.5 hours to obtain an aqueous phase system, and then the aqueous phase system was added to the oil phase, the temperature was raised to 70°C, and the reaction was performed for 6 hours to obtain composite microspheres; The dosage ratio of precursor 1, Tween-20, Span-60 and kerosene is 3.2g:1.5g:1.5g:50mL, the mass fraction of sodium hydroxide solution is 20%, and the dosage ratio of β-cyclodextrin, sodium hydroxide solution, epichlorohydrin and oil phase is 9.8g:50mL:13g:150mL.

[0008] Example 3 A fluid loss reducer and a preparation method thereof, comprising the following steps: weighing the following raw materials in parts by weight: 45 parts of sulfonated humic acid, 12 parts of composite microspheres, 8 parts of block polymers, 0.12 parts of antibacterial agents and 0.3 parts of antioxidants, mixing the sulfonated humic acid, composite microspheres, block polymers, antibacterial agents and antioxidants to prepare a fluid loss reducer; The sulfonated humic acid is sulfonated humic acid produced by Ryan Environmental Protection; The antibacterial agent is Haikuo HK-8360; The antioxidant is BASF Irganox 1330; The block polymer is prepared by the following steps: Step A1: p-nitroaniline, hydrochloric acid solution and deionized water are mixed, and sodium nitrite is added under stirring at a rate of 180 rpm and a temperature of 5° C., and stirred for 20 min. Then, sodium hydroxide solution and phenol are added, and the temperature is raised to room temperature, and the reaction is carried out for 2 h to obtain intermediate 1. 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and tetrahydrofuran are mixed, and intermediate 1 is added under stirring at a rate of 120 rpm and room temperature, and the reaction is carried out for 4 h to obtain intermediate 2; The mass fraction of hydrochloric acid solution is 35%, the molar concentration of sodium hydroxide solution is 2 mol / L, the amount ratio of p-nitroaniline, hydrochloric acid solution, deionized water, sodium nitrite, sodium hydroxide solution and phenol is 0.054 mol: 18 mL: 25 mL: 0.055 mol: 48 mL: 0.054 mol; the amount ratio of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate 1 is 0.015 mol: 2 g: 0.12 g: 0.015 mol; Step A2: Intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and deionized water were mixed, stirred and azobisisobutyronitrile was added under nitrogen protection at 70°C, and reacted for 8 hours to obtain a block polymer; The ratio of intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile is 0.001 mol: 0.012 mol: 0.3 mol: 0.1 mol: 0.01 g; The composite microspheres are prepared by the following steps: Step B1: Humic acid and potassium hydroxide solution were mixed, stirred at a stirring rate of 200 rpm, and ferric nitrate solution was added at room temperature, stirred for 20 minutes, then heated to 125° C., reacted for 4 hours, then sodium montmorillonite was added, ultrasonically dispersed for 20 minutes, and then continued to react for 3 hours to obtain precursor 1; The molar concentration of potassium hydroxide solution is 4 mol / L, the molar concentration of ferric nitrate solution is 0.25 mol / L, and the dosage ratio of humic acid, potassium hydroxide solution, ferric nitrate solution and sodium montmorillonite is 1 g: 8 mL: 240 mL: 3.5 g; The humic acid is Ryan environmentally friendly humic acid; The sodium montmorillonite is Borui 800 mesh sodium montmorillonite; Step B2: Precursor 1, Tween-20, Span-60 and kerosene were mixed, stirred at a stirring rate of 800 rpm at room temperature for 30 minutes to obtain an oil phase, β-cyclodextrin and sodium hydroxide solution were mixed, stirred at a stirring rate of 180 rpm at room temperature, and epichlorohydrin was added to react for 2 hours to obtain an aqueous phase system, and then the aqueous phase system was added to the oil phase, the temperature was raised to 70° C., and the reaction was performed for 8 hours to obtain composite microspheres; The dosage ratio of precursor 1, Tween-20, Span-60 and kerosene is 3.5g:2g:2g:50-60mL, the mass fraction of sodium hydroxide solution is 20%, and the dosage ratio of β-cyclodextrin, sodium hydroxide solution, epichlorohydrin and oil phase is 10.4g:60mL:14g:160mL.

[0009] Comparative Example 1 Compared with Example 3, this comparative example is different in that the intermediate 1 of Example 3 is replaced by phenol during the preparation of the block polymer of Example 3, and the other steps are the same.

[0010] Comparative Example 2 Compared with Example 3, this comparative example is different in that the precursor 1 of Example 3 is replaced with Borui 800 mesh sodium-based montmorillonite in the process of preparing composite microspheres in Example 3, and the other steps are the same.

[0011] Take the fluid loss reducers prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, mix the fluid loss reducers with water, stir for 30 minutes at room temperature to obtain a mixed solution, refer to GB / T 16783.1-2014, 600mL deionized water, 22g bentonite and 4g anhydrous sodium carbonate were stirred for 60min at a stirring rate of 6000rpm to prepare a fresh water slurry, 1.5% of the mixed solution was added to the fresh water slurry, mixed and stirred, and hot rolled at 140℃ for 16h, and the filtration loss at 30min was measured, and then the filtration loss at 180℃ for 16h was measured at 30min to evaluate its high temperature resistance, 30% of sodium chloride and 1% of calcium chloride were added to the fresh water slurry to prepare a salt water slurry, and the filtration loss at 30min after hot rolling at 180℃ for 16h in the salt water slurry was measured to evaluate its salt and calcium resistance. The test results are shown in Table 1. Table 1 Test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Fresh water slurry 140℃ filtration loss (mL) 10.8 10.6 10.5 13.5 10.7 Fresh water slurry 180℃ filtration loss (mL) 11.7 11.8 11.6 14.7 13.8 Filtration loss of salt water slurry at 180℃ (mL) 17.9 17.5 17.4 21.4 19.2 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1 and Comparative Example 2, in Comparative Example 1, the intermediate 1 of Example 3 in the preparation process of the block polymer of Example 3 is replaced with phenol. Due to the lack of azobenzene structure, it is impossible for the host-guest combination to occur, thereby causing its performance to decline. In Comparative Example 2, the precursor 1 of Example 3 in the preparation process of the composite microspheres of Example 3 is replaced with Borui 800 mesh sodium-montmorillonite. Due to the lack of humic acid, it is impossible for it to cross-link, thereby affecting its high temperature resistance.

[0012] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0013] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a fluid loss reducer, characterized in that: The method comprises the following steps: weighing the following raw materials in parts by weight: 40-45 parts of sulfonated humic acid, 10-12 parts of composite microspheres, 6-8 parts of block polymers, 0.1-0.12 parts of antibacterial agents and 0.2-0.3 parts of antioxidants, mixing the sulfonated humic acid, composite microspheres, block polymers, antibacterial agents and antioxidants to prepare a fluid loss reducer; The block polymer is prepared by the following steps: Step A1: p-nitroaniline, hydrochloric acid solution and deionized water are mixed, and sodium nitrite is added under stirring at a rate of 150-180 rpm and a temperature of 0-5° C., and the mixture is stirred for 15-20 min. Then, sodium hydroxide solution and phenol are added, and the mixture is heated to room temperature and reacted for 1.5-2 h to obtain intermediate 1. 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and tetrahydrofuran are mixed, and intermediate 1 is added under stirring at a rate of 100-120 rpm and room temperature, and the mixture is stirred for 3-4 h to obtain intermediate 2; Step A2: Mix the intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and deionized water, stir and add azobisisobutyronitrile under nitrogen protection at 70°C, and react for 6-8h to obtain a block polymer; The composite microspheres are prepared by the following steps: Step B1: humic acid and potassium hydroxide solution are mixed, stirred at a stirring rate of 180-200 rpm, and ferric nitrate solution is added at room temperature, stirred for 15-20 minutes, then heated to 120-125° C., reacted for 3-4 hours, then sodium montmorillonite is added, ultrasonically dispersed for 20 minutes, and then the reaction is continued for 2-3 hours to obtain precursor 1; Step B2: Precursor 1, Tween-20, Span-60 and kerosene are mixed, stirred at a stirring rate of 600-800 rpm, at room temperature, and stirred for 25-30 minutes to obtain an oil phase, β-cyclodextrin and sodium hydroxide solution are mixed, stirred at a stirring rate of 150-180 rpm, at room temperature, and epichlorohydrin is added, and the reaction is carried out for 1.5-2 hours to obtain an aqueous phase system, and then the aqueous phase system is added to the oil phase, the temperature is raised to 70°C, and the reaction is carried out for 6-8 hours to obtain composite microspheres.

2. The method for preparing a fluid loss reducer according to claim 1, characterized in that: In step A1: the mass fraction of the hydrochloric acid solution is 35%, the molar concentration of the sodium hydroxide solution is 2 mol / L, the amount ratio of p-nitroaniline, hydrochloric acid solution, deionized water, sodium nitrite, sodium hydroxide solution and phenol is 0.05-0.054 mol: 15-18 mL: 20-25 mL: 0.054-0.055 mol: 45-48 mL: 0.05-0.054 mol; the amount ratio of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and intermediate 1 is 0.012-0.015 mol: 1.8-2 g: 0.1-0.12 g: 0.012-0.015 mol.

3. The method for preparing a fluid loss reducer according to claim 1, characterized in that: In step A2, the ratio of intermediate 2, N-vinyl pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and azobisisobutyronitrile is 0.0008-0.001 mol: 0.01-0.012 mol: 0.28-0.3 mol: 0.09-0.1 mol: 0.01 g.

4. The method for preparing a fluid loss reducer according to claim 1, characterized in that: In step B1, the molar concentration of the potassium hydroxide solution is 4 mol / L, the molar concentration of the ferric nitrate solution is 0.25 mol / L, and the dosage ratio of humic acid, potassium hydroxide solution, ferric nitrate solution and sodium montmorillonite is 0.8-1 g: 5-8 mL: 220-240 mL: 3.2-3.5 g.

5. The method for preparing a fluid loss reducer according to claim 1, characterized in that: In step B2: the amount ratio of precursor 1, Tween-20, Span-60 and kerosene is 3.2-3.5g:1.5-2g:1.5-2g:50-60mL, the mass fraction of sodium hydroxide solution is 20%, and the amount ratio of β-cyclodextrin, sodium hydroxide solution, epichlorohydrin and oil phase is 9.8-10.4g:50-60mL:13-14g:150-160mL.

6. A fluid loss reducer, characterized in that: Prepared according to any one of the preparation methods described in claims 1-5.

Citation Information

Patent Citations

  • Salt-resistant high-temperature-resistant filtrate reducer and preparation method thereof

    CN110607169A

  • Reservoir drilling fluid system and preparation method thereof

    CN114539994A

  • Deep-well polysulfonate drilling fluid and preparation method therefor

    WO2019010771A1